2013
DOI: 10.1007/s00586-013-2881-7
|View full text |Cite
|
Sign up to set email alerts
|

3D analysis of brace treatment in idiopathic scoliosis

Abstract: Purpose We have evaluated the effect of bracing in scoliosis on coronal alignment in a cohort of patients. Current literature has not described the specific effect of bracing on the 3D shape of the scoliotic curves. The purpose of this study was to analyze the variability of the 3D effect of bracing on idiopathic scoliosis. Materials and methods The spines of 30 patients with adolescent idiopathic scoliosis were reconstructed using biplanar stereoradiography with and without the brace. The Cobb angle, sagittal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 19 publications
5
50
0
Order By: Relevance
“…Seven (22%) of the patients were found to have thoracic flat back, but 3 of them had it before treatment. A previous study by Courvoisier et al 4 on the immediate correction provided by brace treatment showed significant decreases in LL but no statistical difference in TK. However, progressive modifications of the spine may occur throughout the treatment period.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Seven (22%) of the patients were found to have thoracic flat back, but 3 of them had it before treatment. A previous study by Courvoisier et al 4 on the immediate correction provided by brace treatment showed significant decreases in LL but no statistical difference in TK. However, progressive modifications of the spine may occur throughout the treatment period.…”
Section: Discussionmentioning
confidence: 80%
“…A previous study found no statistically significant immediate modification of transverse plane parameters. 4 Lebel et al 11 compared the differences in immediate 3D effects between the Chêneau brace and the Boston brace by assessing 3D reconstructions. They demonstrated that the Chêneau brace had a significant de-rotation effect compared with the Boston brace.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements are now allowing true 3D assessment of scoliosis and are causing a fundamental shift in how we think about assessment, treatment, and prognosis. Work by Courvoisier et al has demonstrated that the EOS 3D radiography system (EOS Imaging) can be used to assess the efficacy of a brace-measuring correction of rotational deformity in addition to Cobb angle [10,11]. Courvoisier et al and Nault et al have used EOS to show that measures of transverse-plane deformity correlate strongly with progression [9,24,25].…”
Section: Predictor Variables Considered and Selectedmentioning
confidence: 96%
“…Low-dose bi-planar radiographs can be used in routine clinical practice to assess patient specific spinal geometry during conservative treatment, allowing better description of the correction in three dimensions [6]. Testing different brace designs in order to optimize correction, however, requires multiple radiographic images; radiation doses can then accumulate over the several years that are often needed for this treatment.…”
Section: Introductionmentioning
confidence: 99%